2010
DOI: 10.2341/09-135-l
|View full text |Cite
|
Sign up to set email alerts
|

Amalgam Repair: Quantitative Evaluation of Amalgam-resin and Resin-tooth Interfaces with Different Surface Treatments

Abstract: In terms of microleakage reduction, etch & rinse adhesives may be preferred over self-etch adhesives for amalgam repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
13
2
Order By: Relevance
“…In contrast, Cehreli et al (2010) 14 demonstrated that microleakage at the amalgam/composite resin interface was higher than at the tooth interface, but dealt with old amalgam as a substrate. It seems that use of fresh amalgam is favorable in terms of sealing ability at the interface of an amalgam/ composite combined restoration.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, Cehreli et al (2010) 14 demonstrated that microleakage at the amalgam/composite resin interface was higher than at the tooth interface, but dealt with old amalgam as a substrate. It seems that use of fresh amalgam is favorable in terms of sealing ability at the interface of an amalgam/ composite combined restoration.…”
Section: Resultsmentioning
confidence: 97%
“…This has been attributed to the non-uniform stresses generated with shear testing within the interfacial zone as this can have a significant effect on the mode of failure. 24 The basis for selection of the adhesive repair systems used in the current study was their demonstrated ability to bond to metals 25 , their use in similar studies involving amalgam 6,9,21,26 and their commercial availability as products marketed for facilitating intra-oral amalgam repairs.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Another common reason for amalgam replacement is partial or complete cusp fracture adjacent to, or involving, the amalgam restorations. 6,7 Previous studies indicate that complete cusp fracture in teeth restored with amalgam restorations is a relatively common observation in clinical practice and particularly so for posterior teeth restored with extensive amalgam restorations. [7][8][9] The prevalence of complete cusp fracture in amalgam-restored premolar and molar teeth has been reported to range between 4-8% and 5-15% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The cohesive fractures better demonstrated the effectiveness of the surface treatment 11,[30][31][32] . On the other hand, we observed that the groups with low bond strength had more adhesive fractures.…”
Section: Discussionmentioning
confidence: 92%